Breast augmentation with silicone implants performed without drainage - retrospective analysis of 726 cases - Stepić Nenad; Končar Jovana; Rajović Milica; Novaković Sanja; Novaković Marijan (Vojnosanitetski Pregled)
Introduction: Breast augmentation has been one of the most popular aesthetic procedures. Early complications, like infection, seroma, hematoma and capsular contracture like one of the most frequent long term complication, might be related to wound drainage. Aim of the study was to investigate the rate of the complications of breast augmentation procedure performed without drainage. Material and Methods. Retrospective analysis of all patients underwent breast augmentation in the period of 2003-2013 was performed. From the medical history of the patients, data related to demographic characteristics of the patients, surgical technique and rate of complications were collected. Wound drainage has not been used in any of the patients. Patients were followed at the discharge, after 7 days, three months and yearly thereafter. Wound seroma, wound hemathoma, wound infection and capsular contracture were followed. Results. There were 726 patients with average age of 28,5 year (22-48). Breast augmentation using silicone implants was performed with inframammary approach using subglandular, submuscular and dual plane technique. Average implant size was 339cc (200-520). Subglandular augmentation had 545 (75%), while, 181 (25%) received an implant in submuscular plane. Those, who were operated with dual plane technique were 86 (47,5%).In early postoperative period, there was no infection, five seromas (0,7 %) and eight hematoma (1,1%), while five of them required surgical evacuation. There was no statistical significant difference between the two surgical techniques in terms of complication rate. During follow up, there were three capsular contractures (0,4%). Conclusions. The incidence of complications in our group of patients after breast augmentation is low even though no drainage was used. Still, further randomized trials are needed to prove role of drainage in prevention of complications after breast augmentation.